2023
DOI: 10.1039/d2an02051c
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and comparative analysis of Aconitum alkaloids in Fuzi using DESI-MSI and UHPLC-QTOF-MS

Abstract: Spatial distribution of Aconitum alkaloids (AAs) in raw Fuzi and content changes after processing by DESI-MSI and UHPLC-QTOF-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The results revealed that the content of less toxic MDAs and NAs, converted from the more toxic DDAs, increased in all processed products. Additionally, the content of benzoylaconine increased post-processing, indicating enhanced pharmacological activity and reduced toxicity ( Ren et al, 2023 ). Furthermore, processed Fuzi can elevate testosterone, superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT) levels while decreasing malondialdehyde levels in serum compared to raw Fuzi, thereby mitigating the reproductive toxicity and genotoxicity of Fuzi.…”
Section: Herbal Processingmentioning
confidence: 99%
“…The results revealed that the content of less toxic MDAs and NAs, converted from the more toxic DDAs, increased in all processed products. Additionally, the content of benzoylaconine increased post-processing, indicating enhanced pharmacological activity and reduced toxicity ( Ren et al, 2023 ). Furthermore, processed Fuzi can elevate testosterone, superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT) levels while decreasing malondialdehyde levels in serum compared to raw Fuzi, thereby mitigating the reproductive toxicity and genotoxicity of Fuzi.…”
Section: Herbal Processingmentioning
confidence: 99%